Investements - Reilly, Frank K. (Dryden Press, 1995)
To help understand how to manage one’s money to derive the most from what you earn, to develop a way of analyzing and thinking about investments, and to pass on the excitement about investing, are the goals the authors have set for this edition. Global investing information, descriptive and theoretical material, practitioner investment techniques, and drawing from knowledge and readings for those preparing for the CFA exams, are highlights of this edition. Reilly and Norton have thoroughly revised, reorganized, and updated material, and cover the major topics logically and concisely, providing a strong base for those who want to do advanced work in investment analysis and valuation.